(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The development and improvement problem of principles and receptions of streettravelling network planning and also facilities of their providing, that would take into account the necessities of all users an environment, is in-process investigated, especially people with different disability nosologies and other categories of people with limited mobility. Distinguished basic groups of principles in relation to planning of environment. Analysed basic principles of planning of street-travelling network for conditioning for unimpeded motion by the community of all participants of traffic participants: functional integration, functional differentiation, compactness, town-planning integrating, microdistricts creation, construction of optimal street-travelling network, functional zoning, non-conflictual, modernisation, aesthetic attractiveness, visual perception, sequentialization, design of spatial corridor, universal design, availability, comfort, informing, unconcern, «smart adaptation», social, social adaptation, participating in public life, labour employment. Keywords: street and road network, people with limited mobility (PLM), transport accessibility, mobility, transport infrastructure, design principles.